Accelerated Arabic Speaking Instruction through a Multiple Intelligences Framework: Innovation and Pedagogical Transformation at an Indonesian Language Center - Amzaludin Amzaludin; R. Taufiqurrochman; Dewi Chamidah; Rico Andrian (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
The growing demand for effective Arabic language instruction has encouraged educational institutions to develop innovative learning models that accelerate communicative competence while accommodating diverse learner characteristics. However, studies examining the integration of accelerated learning and Multiple Intelligences (MI) theory in Arabic speaking instruction remain limited. This study investigates the design and implementation of an MI-based accelerated learning program for Arabic speaking skills at Markaz Arabiyah Kediri, Indonesia. Using a qualitative case-study approach, data were collected through observations, semi-structured interviews with institutional leaders, instructors, staff, and students, as well as document analysis. The data were analyzed through data reduction, categorization, interpretation, and verification. The findings indicate that the AKBARNAS program is an intensive competency-based acceleration model that promotes authentic communication through dialogue, presentations, debates, and collaborative interaction. The program systematically integrates various domains of intelligence, including linguistic, logical-mathematical, bodily-kinesthetic, visual-spatial, and naturalistic intelligences, into instructional and assessment activities. This integration contributes to improved speaking fluency, grammatical accuracy, confidence, engagement, and critical thinking skills among learners. The study highlights the potential of MI-based accelerated learning as an innovative pedagogical framework that aligns instructional intensity with learner diversity, offering valuable insights for advancing communicative Arabic language education in diverse educational settings.